Identifikasi Biota Asosiasi Pada Mangrove Jenis Avicennia spp. dan Sonneratia spp. di Pantai Laksamana Kabupaten Batu Bara - Fajri, Surya; Gunawan, Heru; Puspitasari, Dian; Ningrum, Hesti Sulistia; Nizirwan, Muhammad Iqbal; Firmansyah, Mhd Adi; Hardiansyah, Hardiansyah; Pahmi, Pahmi; Wahyudi, Akmal (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Mangroves are one of the most important natural ecosystems. Mangroves physically function as land protection areas against the impact of abrasion and erosion due to waves. In terms of chemistry, mangroves act as filters for pollutants, especially organic materials, and as an energy source that provides detritus, which is a food source for aquatic organisms. Aquatic biota that live in mangrove areas include mollusks, crabs, fish, oysters, and shrimp. In addition, the role of mangroves is very significant in maintaining the productivity of waters in coastal areas and supporting the lives of surrounding communities. The purpose of this study is to identify biota whose lives are associated with mangroves of Avicennia spp. and Sonneratia spp. The method used in this study is exploration. The location of the transect is made based on the purposive sampling method, where data is taken deliberately based on the abundance of biota and mangroves of the species Avicennia spp. and Sonneratia spp. The types of biota associations Nerita polita, Turritella attenuata, Chicoreus sp., Mytilus edulis, Geloina expansa, Scylla tranquebarica, Leptuca uruguayensis, Aratus pisonii, and Lepas balanoides. Mangroves associated with the above biota are from the types of Sonneratia alba and Avicennia marina.